Nitrogen Metabolism Disorder Accelerates Occurrence and Development of Lung Adenocarcinoma: A Bioinformatic Analysis and In Vitro Experiments - Zhang, Zexin; Xiahou, Zhikai; Wu, Wenfeng; Song, Yafeng (Frontiers in Oncology, 2022)
Background: Nitrogen metabolism (NM) plays a pivotal role in the occurrence and development of cancer and immune regulation. We aimed to construct a prognostic model and nomogram using NM-related genes to apply in the evaluation of patients with lung adenocarcinoma (LUAD). Methods: The differentially expressed genes (DEGs) related to NM were acquired from The Cancer Genome Atlas (TCGA) database. Consistent clustering analysis was used to divided it into different modules and then performed survival analysis and differentially expressed analysis. Survival information of patients was combined with the expression of NM-related genes that extracted from TCGA and Gene Expression Omnibus (GEO) databases. Subsequently, Univariate cox analysis and Least absolute shrinkage and selection operator (LASSO) regression were used to built a prognostic model. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis elaborated the mechanisms of NM disorder (NMD). Meanwhile, immune cells and immune functions related to NMD was also discussed. Univariate cox analysis and multivariate cox analysis identified independent risk factors and constructed a nomogram. Finally, real-time fluorescent quantitative PCR (RT-PCR) and western bolt (WB) were used to verify the expressed levels of hub genes. Results：A total of 138 differential NM-related genes was divided into two gene modules. 16 NM-related genes were used to built a prognostic model and receiver operating characteristic curve (ROC) showed that the efficiency was reliable. GO and KEGG analysis suggested that NMD accelerated occurrence and development of LUAD may through Wnt signaling pathway. The levels of activation dendritic cells (aDCs) and Type II interferon response of the low risk group higher than the high risk group indicated that a better survival prognosis. ABCC2, HMGA2 and TN stages were identified as independent risk factors and used to construct a nomogram. Finally, RT-PCR and WB showed that CDH17, IGF2BP1, IGFBP1, ABCC2, and HMGA2 was significantly different expressed between human lung fibroblast (HLF) cell and cancer cells. Conclusions: High risk of NM levels was reveal to a poor prognosis of LUAD. NMD may regulate immune system through affecting aDCs and Type II interferon response. The prognostic model was able to effectively evaluate the outcomes of patients.